PENGARUH CONTROLLABILITY ATTRIBUTION DAN STABILITY ATTRIBUTION TERHADAP SATISFACTION MELALUI FIRM RESPONSIBILITY DAN RECOVERY EXPECTATION - Ahmad Sukmawan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2009)
Objectives of this research was to investigate how and why other-customer misbehavior has a negative influence on customer satisfaction with the service firm. The design of this research applies a survey in Telkomsel to interview the customers for testing the hypothesis. Meanwhile the required data consist of five variables are controllability attribution, stability attribution as independent variables, firm responsibility, and recovery expectation as intervening variable. Finally, satisfaction as dependent variable. The aggregate numbers of customer being respondent of the study are 130 customers. Data analysis used in this research was consists of Structural Equation Modelling by AMOS 6.0 as software. Result of this research concludes that people consider another customer's failure to be the firm's responsibility when they perceive that the failure is under the firm's volitional control (i.e. controllability attribution). This controllability attribution leads to customer expectations of compensation for recovery from dissatisfaction.Keywords: Call center, customer service, controllability attribution, service satisfaction, recovery expectation.